1998
DOI: 10.1038/sj.bmt.1701491
|View full text |Cite
|
Sign up to set email alerts
|

Autologous peripheral blood stem cell transplantation in acute myeloblastic leukaemia and myelodysplastic syndrome patients: evaluation of tumour cell contamination of leukaphereses by cytogenetic and molecular methods

Abstract: Summary:We evaluated 18 acute myeloblastic leukaemia (AML) and myelodysplastic syndrome (MDS) patients with abnormal karyotype at diagnosis who underwent peripheral blood stem cell (PBSC) transplantation. To evaluate the presence of residual tumour cells, bone marrow (BM) samples and PBSC collections were analysed by cytogenetics and in selected cases also by fluorescence in situ hybridisation (FISH) and molecular studies. All patients were considered to be in morphologic and cytogenetic complete remission (CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…When applicable, cytogenetic and molecular analyses were performed on the product in order to confirm CR. 22 …”
Section: Leukapheresis Procedures and Pbsc Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…When applicable, cytogenetic and molecular analyses were performed on the product in order to confirm CR. 22 …”
Section: Leukapheresis Procedures and Pbsc Processingmentioning
confidence: 99%
“…Studies [20][21][22] have failed to detect tumor cells in the peripheral blood of leukemic subjects during the early recovery phase from induction/consolidation chemotherapy. However, the high relapse rate previously described 13,15,23,24 suggests that the much larger number of cells infused with PBSC may result in reinfusion of more residual malignant cells.…”
mentioning
confidence: 99%
“…3)(q26;q21q26)를 동반하는 혈액질환이다 [1]. 세 염색체 이상은 모두 3q21의 ribophorin I (RPN1) 유전자의 증강인자(enhancer) 가 3q26에 위치한 ecotropic viral integration site-1 (ETV1) 유 Background : 3q21q26 syndrome includes chromosomal abnormalities of inv(3)(q21q26), t(3;3) (q21;q26), and ins(3;3)(q26;q21q26).…”
Section: 서 론unclassified
“…This finding is in line with the concept that AML with inv(16) is strictly associated with the type A transcript. 6,7 Three patients (Nos 1-3 in Table 1), who were only treated with non-ablative chemotherapy due to their age, died from AML: in these cases MRD was not evaluated. The remaining 16 patients (Nos 4-19) achieved CCR after different schedules of ablative induction and consolidation chemotherapy protocols ( Table 1).…”
Section: Molecular Remission In Pcr-positive Acute Myeloid Leukemia Pmentioning
confidence: 99%
“…[2][3][4] The molecular marker is detectable by reverse transcription-polymerase chain reaction assay (RT-PCR) [5][6][7][8][9] on RNA at the time of diagnosis, and could be particularly useful for monitoring MRD in patients who achieve complete clinical remission (CCR) after induction therapy. [10][11][12][13] Marcucci et al 14 and several other authors [10][11][12][13] have reported favorable clinical outcomes despite persistence of CBF␤/MYH11 transcripts detected by RT-PCR; similar findings have been reported for another core-binding-factor altered in AML, 15,16 in which positive expression of AML1-ETO transcript can persist after induction and consolidation chemotherapy without evidence of hematological relapse.…”
Section: Molecular Remission In Pcr-positive Acute Myeloid Leukemia Pmentioning
confidence: 99%